Allergic rhinitis and urticaria burden and antihistamine treatment options in Thailand: A modified Delphi study - Hiroshi Chantaphakul, MD; Chirawat Chiewchalermsri, MD; Dara Mairiang, MD; Mongkol Lao-Araya, MD; Orathai Piboonpocanun, MD; Sira Nanthapisal, MD, PhD; Wat Mitthamsiri, MD; Wasu Kamchaisatian, MD; Wiparat Manuyakorn, MD, PhD; Pasuree Sangsupawanich, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Allergic rhinitis (AR) and chronic urticaria impose significant socioeconomic burdens on lower-income countries. Despite the availability of evidence-based guidelines, their implementation varies, and comprehensive data on these allergic conditions are notably lacking in Thailand. Objectives: We sought to describe current management strategies for AR and urticaria in Thailand. Methods: The Allergy, Asthma, and Immunology Association of Thailand used a modified Delphi method to explore consensus on management strategies for AR and urticaria. Clinicians with expertise in these conditions provided input through a web-based questionnaire. The survey assessed disease burden in Thailand, its impact on quality of life, and the use of H1-antihistimine treatment options. Results: In total, 105 experts, mainly in allergy and immunology, with 70% having more than 10 years of clinical practice, provided input. Consensus was achieved on 22 (88%) of the 25 statements. Second-generation antihistamines were preferred as initial treatment for AR and urticaria because of their reduced sedation and lack of anticholinergic effects. Almost all participants (98.1%) recommended these antihistamines for acute and chronic urticaria. Additionally, 87.6% of the respondents favored up-dosing a single antihistamine agent for managing chronic urticaria. The benefits of orally disintegrating antihistamines were particularly noted for their ease of administration and patient compliance. Conclusion: Results indicate a knowledge gap in evidence-based practices among Thai clinicians. Addressing this gap through enhancing clinical guideline adherence and encouraging pharmacist involvement in patient care can improve access to medication and better disease management, ultimately improving patient outcomes while reducing the socioeconomic burden of AR and urticaria.